Aportaciones para una planificación lingüística en el Alto AragónActitudes de los escolares hacia la lengua minorizada - Campos, I.O. (2019)
In contradistinction to other Spanish plurilingual territories, language planning has hardly been developed in Aragon until now. Nevertheless, in recent years, the institutions have shown a growing interest in this issue. Thus, it is necessary to go deep into the study of the attitudes towards the regional languages among people who would be affected by the future language policies. The main objective of our research is to contribute to this necessary preliminary analysis through the study of Primary Education students’ attitudes towards Aragonese language. In this way, we designed a quantitative research with a sample of 655 schoolchildren from the territory of historical influence of Aragonese language. The results show a general attitude favorable to the regional language and the positive influence of social, family and school contact with this tongue. In addition, the data provide new evidences regarding the weak situation of this language, confirming that only a minority of children from Alto Aragón use it habitually with their family.